'The love is spread out': how birth children talk about their experiences of living with foster children. (July 2019) - Stoneman, Kate; Dallos, Rudi
This article examines the experiences of birth children with a foster child (or children) in their family. Specifically, it explores how birth children's attachment history influences how they discuss their emotional needs and the ways in which attachment strategies help shape the nature of the children's accounts of their experiences. Eight birth children in fostering families were interviewed. These enquired about the children's childhood using questions from attachment interviews, and employed integrated 'sculpts' to explore their experiences of fostering. An attachment-informed Interpretative Phenomenological Analysis (IPA) approach found four superordinate themes: preparation and knowledge about fostering; disruptions to family life; altered roles within families; and making and breaking connections. Additionally, the use of defensive processes was detected in how the children managed the experience; they could minimise their needs and feelings in the family. Such defensive processes are likely to influence how children express their experience of having a foster child in the home. The study was limited by its restricted demographic range ‒ mostly white females. The findings can be used to support birth children in families who foster through increasing preparation, matching foster children to families, providing support around the disruptions to family life and supporting children to say goodbye.